Politicians and police in the face of democratic change in Chile and Colombia - Frühling Ehrlich, Hugo (Policing and society, 2025)
This article draws on theories of institutional change, to offer a comparative analysis of politician-police relationships during processes of political change by examining Carabineros de Chile and the Colombian National Police. It begins with Chile’s transition to a new democratic regime under President Aylwin in 1990. On the other hand, the Colombian case study begins with the debate that led to the approval of a new constitution in 1991. The authors use the analysis of institutional change by [Mahoney, J., and Thelen, K., Eds. 2009. Explaining institutional change: ambiguity, agency, and power. New York: Cambridge University Press], to argue that institutional change is produced by the interaction between the political context, the characteristics of the target institution and the agents of change. The political context may favour institutional change or, conversely, give rise to coalitions with strong veto power. The Carabineros and the Colombian National Police developed strategies to retain influence over the change processes, determining their depth and scope and often straying from the original political objectives. Both institutions aim to strengthen their bureaucratic veto power over time through two fundamental variables, which researchers call police veto power and the administrative and managerial capacity to propose alternative policies to civilian authorities. The mechanisms police use to respond to change proposals are: institutional blocking; strategic policy substitution; negotiated autonomy; and, adaptive implementation.